AGAPE VS PHILIA? THOMAS AQUINAS TENTANG CINTA-KASIH, PERSAHABATAN, DAN KEADILAN - Kristanto, Heribertus Dwi; Stanislaus, Surip (UNIKA Santo Thomas, 2024)
Many Christian writers think of Christian agape love as incompatible with Greek philosophical tradition of love, known as philia (friendship). Agape is seen as a kind of love that is non-preferential, inclusive, altruistic and without regard to self-interest, whereas philia is regarded as a kind love that is preferential, exclusive, egocentric and reciprocal in nature. Agape is thought to have eclipsed philia. Then, in the spirit of agape, justice is understood as impartiality or treating everybody equally. This essay aims to show that according to St. Thomas Aquinas Christian agape love or charity (Latin: caritas) is not only compatible with philia (Latin: amicitia) but instead can be understood as “a friendship between man and God”. As a friendship, charity incorporates essential elements of philia, such as benevolence, mutual love, and some life sharing (communicatio). Perceived as grace, charity acknowledges the presence of order (ordo caritatis), in which justice does not necessarily amount to ‘giving to each the same thing’ (i.e., impartiality), but rather ‘giving to each according to his needs’.